(untitled) (Al-Aasar, 2025)
This study employs a quantitative, corpus-based Critical Discourse Analysis (CDA) to explore the underlying ideological patterns in English textbooks for Grades 1 and 2, published by the Punjab Curriculum and Textbook Board (PCTB) under Pakistan’s Single National Curriculum (SNC) policy. Drawing on Fairclough’s three-dimensional model of CDA comprising textual, discursive, and social analyses the research utilizes corpus linguistic tools such as AntConc, Sketch Engine, and NVivo to examine the linguistic and ideological representations embedded in the texts. The analysis identifies four dominant themes: nationalism, religious ideology, gender roles, and family structures. Findings reveal a consistent portrayal of a unified Pakistani identity characterized by Islamic religiosity, patriarchal gender norms, and traditional family values, with limited representation of diverse or progressive perspectives. Through techniques such as frequency counts, collocation analysis, keyword extraction, and concordance, the study demonstrates how the language of textbooks functions as a vehicle for promoting state-driven ideologies. The research presents empirical evidence emphasizing the need for balanced, inclusive, and intellectually stimulating curricular content. It concludes by discussing policy and pedagogical implications aligned with Pakistan’s Vision 2025 and Sustainable Development Goal 4 (SDG 4), while suggesting future directions for interdisciplinary inquiry.